Determinasi yang Mempengaruhi IPM di Jawa Tengah Tahun 2017-2020 - Leonita Wynne Syaputro (Ecoplan, 2022)
One of the benchmarks to see the quality of human life is the Human Development Index (HDI). The Human Development Index of Central Java Province in 2017-2020 records a positive trend and continues to increase. There are several factors that can affect HDI, including poverty, economic growth, and unemployment. This study aims to determine factors that affect the HDI in Central Java Province in 2017-2020. It employed the panel data regression method with a fixed-effect model. The results showed that poverty, economic growth, and the open unemployment rate concurrently affect the HDI. It was found that poverty has a negative and significant effect on the HDI. Meanwhile, economic growth and the open unemployment rate have a positive and significant effect on the HDI in Central Java.